Tendência epidemiológica da coinfecção tuberculose-HIV no Brasil, entre 2003 e 2013. - Teotonio, Vanessa Luna Araujo (2016)
New HIV-positive cases enhanced 11% from 2005 to 2013 in Brazil. However, there was difference in distribution and evolution between Brazilian regions from 2003 to 2014, increasing 79.7% in Northern region, 30% in Northeastern region, 6.4% in Southern region and 6% in the Midwestern- region; decreasing 26.5% in Southeastern region. According to DATASUS 2014 database, is was also observed an increase in the incidence of tuberculosis (TB) associated with HIV in Brazil. There were 4,905 new registered coinfected cases in 2000, and 6,821 new cases in 2012. HIV infection is one of the main risk factors of TB latent reactivation, due lacking immune response. TB/HIV coinfection induces higher mortality than isolated HIV infection. Given the importance of TB/HIV co-infection, we aimed to analyze space-temporal distribution of TB/HIV coinfection in Brazilian regions from 2003 to 2013. The methods used the ecological study from SINAN secondary data of patients reported with TB/HIV in Brazil in the 2003-2013 periods. The dependent variables were incidence and prevalence rates; proportions of deaths caused by the TB, of tuberculosis cure and of TB treatment dropout among coinfected TB/HIV; and as independent variables, were used socio-demographic characteristics such as gender and age group. The analysis was performed with the estimate of the relative risk for Poisson multilevel analysis, with significance level of 5%. The identification of spatial and space-temporal clusters were conducted through ArcGis 10.1. developed by Esri. The results detected 8% TB/HIV coinfection in Brazil. The highest averages of the incidence and prevalence rates were, respectively, in Southern region (5.92; 8.86 cases/100.000habitants) and Southeastern region (4.38;5.95cases/100.000 habitants). The incidence and prevalence were positively associated to male sex (RR = 3.06) and age 20-59 years old (RR = 11.4), p< 0,001. The highest proportion of death caused by TB in coinfected occurred in Northern region (6.23%), and the lowest in Southern region (2.37%). The TB cure proportion average in TB/HIV coinfection was 46% in Brazil. The highest average of TB cure proportion occurred in Northern region (50%) and the lowest in Northeastern region (41%). The average of TB treatment dropout proportion was 16.5%. The highest average of TB treatment dropout proportion occurred in Northeastern region (18%) and Midwest region had the lowest 13%. The TB cure and TB treatment abandon proportions were negatively associated to the age 20-39 years old (RR = 0.66) and 40-59 years old (RR = 0.71) in relation to younger people. The other group of old people didn¿t present significant statistical association. We conclude that the highest detection rates from TB/HIV coinfection and the worst outcome treatment proportions from TB/HIV coinfection occurred in regions with the worst social and economic levels. After these unfavorable results with regional differences, this study will be useful for planning public health policy in all Brazilian regions.